PARTICIPATORY ACTION RESEARCH SEBAGAI STRATEGI PENGELOLAAN SAMPAH PLASTIK BERKELANJUTAN MELALUI PENGEMBANGAN ECOBRICK - Syukrya Ningsih; Suhendra Suhendra; Bayu Kurniawan; Aini Qomariah Manurung (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2023)
The management of waste at the UIN Sulthan Thaha Saifuddin Jambi Campus is an enormous concern, and a large amount of waste, particularly plastic waste, continues to wind up into landfills. The aim of this research is to use Participatory Action Research (PAR) methods to determine how much plastic trash is generated and whether ecobricks have the potential to help reduce plastic waste. By engaging the academic community in campus waste management through empowerment, capacity building, active participation, and shared experience, this service activity seeks to strengthen the collaboration of the stakeholders involved. It is based on the PAR method, which emphasizes two ideas: action and participation. According on the preliminary mapping findings, it was discovered that plastic accounted for the third-highest percentage of garbage generation—18.86%—followed by plastic bottles—11.45%—of the total waste produced in a day. The second stage involves doing a strategy analysis and concluding with a socialization program for creating ecobricks, which serves as the foundation for change action. One of the best and most environmentally beneficial waste processing techniques is the incorporation of plastic waste management into ecobricks, particularly when combined with a PAR strategy that actively incorporates all campus stakeholders